Corporate social responsibility in the 21st century : debates, models and practices across government, law and business - Horrigan, Bryan (Edward Elgar Publishing Ltd. CheltenhamGB, 2010)
Aims to illuminate and illustrate the insights to be gained from examining corporate social responsibility (CSR) from more than one disciplinary standpoint (e.g. law, business and management), level of analysis (e.g. regulatory theory, standards and practice), occupational role (e.g. lawmakers, corporate regulators and company directors), and jurisdictional perspective (e.g. European and Ango-American standpoints), as an exercise in the scholarship of integration, synthesis and application. Offers a scholarly defence of an aspirational account of CSR. Positions CSR within mainstream corporate responsibility and governance, but also takes a forward-looking approach to CSR's emerging manifestations in the 21st century and what affects its development and application into the future.